Risk Communication for the Future Towards Smart Risk Governance and Safety Management - Bourrier, Mathilde; Bieder, Corinne; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The conventional approach to risk communication, based on a centralized and controlled model, has led to blatant failures in the management of recent safety related events. In parallel, several cases have proved that actors not thought of as risk governance or safety management contributors may play a positive role regarding safety. Building on these two observations and bridging the gap between risk communication and safety practices leads to a new, more societal perspective on risk communication, that allows for smart risk governance and safety management. This book is Open Access under a CC-BY licence.    .
Foreword, by Mathilde Bourrier and Corinne Bieder -- Introduction: Chapter 1 Risk Communication 101: A Few Benchmarks, by Mathilde Bourrier -- Part I Persuading in Peace Time: A Longlasting Story -- Chapter 2 Public Participation in the Debate on Industrial Risk in France: A Success Story?, by Caroline Kamaté -- Chapter 3 Organizing Risk Communication for Effective Preparedness: Using Plans as a Catalyst for Risk Communication, by Amandine Berger-Sabbatel and Benoit Journé -- Chapter 4 Nuclear Crisis Preparedness: Lessons Learned from Fukushima Daiichi, by Geneviève Baumont -- Chapter 5 Risk Communication between Companies and Local Stakeholders for Improving Accident Prevention and Emergency Response, by Michael Baram and Preben Lindoe -- Part II When Reality Strikes Back: Tough Lessons to be Learned from Crises -- Chapter 6 How Risk Communication Can Contribute to Sharing Accurate Health Information for Individual Decision-Making: An Empirical Study from Fukushima During a Post-EmergencyPeriod, by Mariko Nishizawa -- Chapter 7 Crisis Communication During the Ebola Outbreak in West Africa: The Paradoxes of Decontextualized Contextualization, by Loïs Bastide -- Part III The Collapse of Absolute Trust in Absolute Truth.- Chapter 8 Transparency in Healthcare: Disclosing Adverse Events to the Public, by Siri Wiig, Karina Aase, Olav Røise and Mathilde Bourrier -- Chapter 9 How Safety Communication Can Support Safety Management: The Case of Commercial Aviation, by Michel Guérard -- Chapter 10 Risk Communication from an Audit Team to its Client, by Petra Haferkorn -- Conclusion: Chapter 11 Societal Risk Communication - Towards Smart Risk Governance and Safety Management, by Corinne Bieder.   .
Keywords: Security systems; Operations research; Management science; Communication; Security Science and Technology; Operations Research, Management Science; Media and Communication